Ethnobotany of robusta coffee (coffea canephora pierre ex a. froehner) as a spiced coffee drink of the indigenous people of bale village on halmahera island - M. Nasir Tamalene Tamalene; Bahtiar Bahtiar; Suparman Suparman; Slamet Hariyadi (Universitas Negeri Jakarta, 2023)
A study on inherited local knowledge of spiced coffee ethnobotany in processing coffee by the people of Bale Village is necessary to depict the sub-system coffee processing. Bale Village is situated on Halmahera Island. It is one of the villages in the Oba Sub-district, Tidore Kepulauan Regency. The village is known as a producer of coffee bean and coffee powder. This study on local knowledge is an initiative to acquire information on spiced coffee. The research design is a survey design to investigate and document the knowledge of the utilization of spice plants in coffee drinks as a traditional beverage of people in Bale Village. Data are analyzed in a qualitative-thematic manner to describe respondents’ ethnobotanical knowledge and are independent of the researcher’s assessment. The research results indicate that spiced coffee made by the villagers uses six spice plants, namely clove (Syzygium aromaticum (L.), red ginger (Zingiber officinale Roscoe.), cinnamon (Cinnamomum verum J. Presl.), kara benguk (Mucuna pruriens (L.) DC.), nutmeg (Myristica fragrans Houtt.), and pandan (Pandanus amaryllifoliusRoxb.). Stages in the making of spiced coffee with the 5M method include: 1) determine the composition of spiced coffee, 2) grind spiced coffee beans into powder, 3) prepare water, 4) stir the spiced coffee and 5) enjoy the spiced coffee